International migration and transitions to adulthood in Mexico - Avila Sánchez, María de Jesús; Jáuregui Díaz, José Alfredo; Pizarro Hernández, Karina (Universidad Autónoma del Estado de México, 2018)
This research studies the process of transition to adulthood of young Mexicans with migratory experience in the United State and the effect that this displacement had on five transitional events using event history models of continuous time - history history analysis-, using for its elaboration as primary source of information the National Survey of the Youth of the year 2010. The interre-lationship between the different transitional events is also analyzed, comparing the study group with the young without international migration experience in different contexts. The results show that migration experience has an effect on the timing and intensity of the various transitions into adulthood. Migration adds complexity and alter the course of life of young Mexican, limiting the well-being and sustainable development of their future life project.